2005
DOI: 10.1021/jp0519722
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Intramolecular Electron Transfer Reaction of FAD Studied by Magnetic Field Effects on Transient Absorption Spectra

Abstract: The kinetics of intermediates generated from intramolecular electron-transfer reaction by photo irradiation of the flavin adenine dinucleotide (FAD) molecule was studied by a magnetic field effect (MFE) on transient absorption (TA) spectra. Existence time of MFE and MFE action spectra have a strong dependence on the pH of solutions. The MFE action spectra have indicated the existence of interconversion between the radical pair and the cation form of the triplet excited state of flavin part. All rate constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 63 publications
4
77
0
Order By: Relevance
“…In the absence of Trp, the signals at the two wavelengths (red traces in Figs 2a & b) are very similar and differ only in amplitude, reflecting the wavelengthdependence of the extinction coefficients. This indicates that the decay of 3 FAD in the absence of Trp also dominates the 580 nm signal in agreement with Murakami et al 21 In the presence of Trp, the absorbance at 650 nm was rapidly quenched (Fig. 2b) and the amplitude of the slow phase observed at 580 nm increased (Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…In the absence of Trp, the signals at the two wavelengths (red traces in Figs 2a & b) are very similar and differ only in amplitude, reflecting the wavelengthdependence of the extinction coefficients. This indicates that the decay of 3 FAD in the absence of Trp also dominates the 580 nm signal in agreement with Murakami et al 21 In the presence of Trp, the absorbance at 650 nm was rapidly quenched (Fig. 2b) and the amplitude of the slow phase observed at 580 nm increased (Fig.…”
supporting
confidence: 90%
“…20,21 The fluorescence of FAD-Trp solutions at low pH, generated by a 473 nm continuous-wave laser, was monitored by TIRF microscopy ( Fig. 1a) in the presence of a square-wave modulated static magnetic field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar reaction, photoexcited FAD forms an intramolecular triplet SCRP in which the adenine moiety of triplet FAD donates an electron to the isoalloxazine ring [48,49]. Through photochemically induced dynamic nuclear polarization (photo-CIDNP) NMR, Kaptein and colleagues [50,51] demonstrated that the radical pair is produced by photoexcitation in the pH range 1.5-4.0.…”
Section: Photochemistry Of Flavinsmentioning
confidence: 99%
“…p*) (figure 4; [52,53]). For convenience, the third harmonic of the commonly available Nd:YAG laser (l ¼ 355 nm) is typically used to generate the excited singlet flavin which may subsequently form a radical pair with a suitable electron donor [44][45][46]48,49]. When working with cryptochrome and photolyase protein samples, it is important to minimize UV-induced photodegradation, hence care is taken to match the first absorption band more closely using a Nd:YAG pumped dye laser (l % 460 nm) for photoexcitation [54,55].…”
Section: Detection Of Flavin Magnetic Field Effectsmentioning
confidence: 99%